Chemical doping of a core–shell silicon nanoparticles@polyaniline nanocomposite for the performance enhancement of a lithium ion battery anode. Issue 3 (16th December 2015) - Lin, Heng-Yi; Li, Cheng-Hung; Wang, Di-Yan; Chen, Chia-Chun
Abstract : A composite of silicon nanoparticles coated with 5-sulfoisophthalic acid (SPA) doped polyaniline (core/shell SiNPs@PANi/SPA) was prepared and applied as an anode material for lithium ion battery applications. Abstract : New silicon based anodic materials in lithium ion batteries (Si-based LIBs) have been developed worldwide to overcome capacity decay during the lithiation/delithiation process. In this study, a composite of Si nanoparticles coated with 5-sulfoisophthalic acid (SPA) doped polyaniline (core/shell SiNPs@PANi/SPA) was prepared and applied as an anode material for LIB applications. The detailed structure of the core/shell SiNPs@PANi/SPA composite was characterized using high-resolution scanning electron microscopy before and after charging/discharging. The electrochemical measurements showed that the SiNPs@PANi/SPA anode exhibited a high capacity of 925 mA h g −1 and high coulombic efficiency (99.6%) after long-term cycling (1000 cycles). Overall results indicated that the SPA doped polyaniline served as a conductive matrix to improve electrical contact and to provide an adhesive force in Si-based LIBs. Our approach opens a route for the design of efficient silicon nanocomposites for LIB applications.